Antifungal Potential of Marine Organisms of the Yucatan Peninsula (Mexico) against Medically Important Candida spp. - Pech-Puch, Dawrin (2023)
Funding Information: The authors acknowledge the Fundação para a Ciência e a Tecnologia, I.P., through (i) MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020), (ii) LS4FUTURE Associated Laboratory (LA/P/0087/2020), (iii) POPH (Programa Operacional Potencial Humano), and FSE (European Social Fund) CEEC 2017 Initiative (to O.A.L.-R.) and (iv) PhD fellowship to A.P. (SFRH/BD/148854/2019). D.P.-P was the recipient of a postdoctoral fellowship from the National Council of Science and Technology (CONACYT) of Mexico. Publisher Copyright: © 2023 by the authors.